Akkermansia and its metabolites play key roles in the treatment of campylobacteriosis in mice - Jiang, Lai; Yuan, Chunchun; Ye, Wenxin; Huang, Qixin; Chen, Zhuo; Wu, Wenzi; Qian, Lichun (Frontiers in Immunology, 2023)
Campylobacter jejuni (C. jejuni) is a common food-borne bacterial pathogen that can use the host's innate immune response to induce the development of colitis. There has been some research on the role of normal intestinal flora in C. jejuni-induced colitis, but the mechanisms that play a central role in resistance to C. jejuni infection have not been explored.We first investigated the therapeutic effect of FMT on C. jejuni infection. The results showed that FMT significantly reduced the inflammatory response and blocked the invasion of C. jejuni into the colonic tissue. We observed a significant increase in the abundance of Akkermansia in the colon of mice after FMT, as well as a significant increase in the levels of butyric acid and deoxycholic acid. We next demonstrated that oral administration of sodium butyrate or deoxycholic acid had a similar therapeutic effect. Further proteomic analysis showed that C. jejuni induced colitis mainly through activation of the PI3K-AKT signaling pathway and MAPK signaling pathway, whereas Akkermansia, the core flora of FMT, and the gut microbial metabolites butyric acid and deoxycholic acid both inhibited these signaling pathways to counteract the infection of C. jejuni and alleviate colitis. Finally, we verified the above idea by in vitro cellular assays. In conclusion, FMT is highly effective in the treatment of colitis caused by C. jejuni, with which Akkermansia and butyric and deoxycholic acids are closely associated.The present study demonstrates that Akkermansia and butyric and deoxycholic acids are effective in the treatment of colitis caused by C. jejuni. This is the first time that Akkermansia has been found to be effective in fighting pathogens, which provides new ideas and insights into the use of FMT to alleviate colitis caused by C. jejuni and Akkermansia as a treatment for intestinal sexually transmitted diseases caused by various pathogens.